2023
DOI: 10.1371/journal.pone.0279850
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography evaluation of risk factors for an undesirable buccal split during sagittal split ramus osteotomy

Abstract: Sagittal split ramus osteotomy (SSRO) sometimes induces an irregular split pattern referred to as a bad split. We investigated the risk factors for bad splits in the buccal plate of the ramus during SSRO. Ramus morphology and bad splits in the buccal plate of the ramus were assessed using preoperative and postoperative computed tomography images. Of the 53 rami analyzed, 45 had a successful split, and 8 had a bad split in the buccal plate. Horizontal images at the height of the mandibular foramen showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This advantage may be of particular interest in bone surgery, where a particular geometric design of the osteotomy is required [65]. BSSO sometimes induces an irregular ramus splitting pattern, referred to as a bad split, with results indicating that a ramus shape in which the width becomes thinner posteriorly (shorter ramus and low thickness of the buccolingual alveolar region distal to the second molar) often induces bad splits in the buccal plate of the ramus during surgery [66,67]. A study of bone mineral density and muscle mass in adults with developmental skeletal discrepancies showed that 45.7% of the case group were osteopenic or osteoporotic and had significantly lower muscle mass, increasing the risk of bad splits [68].…”
Section: Discussionmentioning
confidence: 99%
“…This advantage may be of particular interest in bone surgery, where a particular geometric design of the osteotomy is required [65]. BSSO sometimes induces an irregular ramus splitting pattern, referred to as a bad split, with results indicating that a ramus shape in which the width becomes thinner posteriorly (shorter ramus and low thickness of the buccolingual alveolar region distal to the second molar) often induces bad splits in the buccal plate of the ramus during surgery [66,67]. A study of bone mineral density and muscle mass in adults with developmental skeletal discrepancies showed that 45.7% of the case group were osteopenic or osteoporotic and had significantly lower muscle mass, increasing the risk of bad splits [68].…”
Section: Discussionmentioning
confidence: 99%